Oil‐Repellent Optics for Wastewater Sensor Applications: A systematic combination of nano‐roughness and adapted coatings. Issue 1 (9th February 2018) - Oberbillig, Thomas; Felde, Nadja; Franz, Martin; Coriand, Luisa; Dahms, Nancy; Munderloh, Karin; Schultz, Karin; Fliedner, Michael; Duparré, Angela
Abstract: A fundamental issue for the identification of environmental problems is the early detection of chemical water pollutants. To guarantee reliable measurement results and to reduce maintenance costs, soiling of the sensor surfaces should be minimized. This work presents a method for fabrication of optical and oil‐repellent functional surfaces, realized by combination of statistically produced nano‐roughness with adapted coating materials.